Prognostic value of folate-associated gene expression in stage II colon cancer - Donia Kaidi; Elisabeth Odin; Yvonne Wettergren; Elinor Bexe Lindskog (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Prognostic variability in stage II colon cancer underscores the need for better risk stratification. Analyzing folate-associated gene expression in stage II colon cancer could provide researchers and clinicians with deeper insights into tumor biology and potentially aid in identifying early prognostic and/or predictive biomarkers. Methods Patients with stage II colon cancer and recurrence (n = 48) were matched to patients with a 5 year recurrence-free follow-up (n = 133). Gene expression of ABCC3, AMT, FPGS, GGH, MFT, PCFT, RFC-1, and TYMS was analyzed in tumor tissue and matching colon mucosa using qPCR and evaluated in relation to time to recurrence (TTR), as well as to demographic and clinicopathological variables. Results Independent of other covariates, TYMS expression in tumors, pT4 stage, and emergency surgery were associated with TTR. There were significant differences in expression levels of all examined genes between tumor and mucosa. ABCC3, GGH, and RFC-1 expression levels differed in mucosa between microsatellite instability-high (MSI-H) compared to microsatellite stable/microsatellite instability-low (MSS/MSI-L) tumors, whereas tumoral expression of AMT, GGH, and TYMS differed between MSI-H and MSS/MSI-L tumors. Depending on tumor location, the expression of ABCC3, AMT, GGH, and RFC-1 in mucosa, as well as the tumoral expression of AMT, GGH, PCFT and RFC-1 differed. Conclusion Low tumoral expression of TYMS was associated with worse TTR, independent of MSI status, pT stage, and emergency surgery. The indication of a better outcome for patients with MSI-H status and high tumoral TYMS expression might be of particular interest in the stratification of patients for immunotherapy.